2020
DOI: 10.1124/jpet.120.000367
|View full text |Cite
|
Sign up to set email alerts
|

Self-Administration of Cotinine in Wistar Rats: Comparisons to Nicotine

Abstract: Nicotine is the major addictive component in tobacco. Cotinine is the major metabolite of nicotine and a weak agonist for nicotinic acetylcholine receptors (nAChRs). Nicotine supports self-administration in rodents However, it remains undetermined whether cotinine can be selfadministered. This study aimed to characterize cotinine self-administration in rats, to compare effects of cotinine to those of nicotine, and to determine potential involvement of nAChRs in cotinine's effects. Adult Wistar rats were traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 53 publications
(66 reference statements)
2
36
1
Order By: Relevance
“…In a recent study, we demonstrated that cotinine was self-administered intravenously in rats in a dose-dependent manner ( Ding et al, 2021 ). Rats acquired self-administration of cotinine over time and responded more on an active lever than an inactive lever.…”
Section: Behavioral Effects Of Cotininementioning
confidence: 99%
“…In a recent study, we demonstrated that cotinine was self-administered intravenously in rats in a dose-dependent manner ( Ding et al, 2021 ). Rats acquired self-administration of cotinine over time and responded more on an active lever than an inactive lever.…”
Section: Behavioral Effects Of Cotininementioning
confidence: 99%
“…The half-life of cotinine is longer than nicotine and its residence time in the bloodstream is 48-96 hours. Since blood cotinine level is proportional to exposure to cigarette, cotinine levels are evaluated as an indicator of nicotine exposure (10,23).…”
Section: E a R L Y A C C E S Smentioning
confidence: 99%
“…One of the most important biomarkers is nicotine and its metabolites (8,9). In humans, more than 80% of nicotine is metabolized to cotinine (10,11). Generally, nicotine is absorbed as particle-bounded or vapor phase by the body.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations